Knockdown of lncRNA H19 suppresses endometriosis in vivo - Liu,Songping (2021)
The long noncoding RNA (lncRNA) H19 is involved in the pathogenesis of endometriosis by modulating the proliferation and invasion of ectopic endometrial cells in vitro, but related in vivo studies are rare. This study aimed to investigate the role of lncRNA H19 in a nude mouse model of endometriosis. Ectopic endometrial stromal cells (ecESCs) were isolated from ectopic endometrium of patients with endometriosis and infected with lentiviruses expressing short hairpin RNA (shRNA) negative control (LV-NC-shRNA) or lncRNA-H19 shRNA (LV-H19-shRNA). The ecESCs infected with LV-NC-shRNA and LV-H19-shRNA were subcutaneously implanted into forty 6- to 8-week-old female nude mice. The size and weight of the endometriotic implants were measured at 1, 2, 3, and 4 weeks after implantation and compared, and lncRNA H19 levels in endometriotic implants were evaluated using real-time polymerase chain reaction (RT-PCR). All nude mice survived the experimental period, and no significant differences in body weight were observed between the experimental group and the control group. All nude mice developed histologically confirmed subcutaneous endometriotic lesions with glandular structures and stroma after 1 week of implantation. The subcutaneous lesions in the LV-NC-shRNA group after 1, 2, 3, and 4 weeks of implantation were larger than those in the LV-H19-shRNA group, and lncRNA H19 levels in subcutaneous lesions in the LV-NC-shRNA group were significantly higher than those in the LV-H19-shRNA group. Knockdown of lncRNA H19 suppresses endometriosis in vivo. Further study is required to explore the underlying mechanism in the future.